KOMPONEN PEMBENTUK RUANG KOTA ALUN-ALUN CIANJUR - Wibowo, Heru; Marwoto, Marwoto; Putra, Wahyu Buana (Jurnal Arsitektur ARCADE, 2022)
Abstract: One of the cities having a historically significant public square is Cianjur Regency. Since the royal era, colonial era, and up to the present, the square has served as the distinguishing feature of the center of the royal authority. The layout of the square space fluctuates depending on the prevailing political ideologies. This study employs an exploratory methodology and approaches for gathering data from field observations. Cianjur Square contains seven of the eight elements that make up urban space, including: (a) changes in land use; (b) The building mass configuration is fixed and the shape of the space is no longer symmetrical like the original form; (c) Parking and circulation areas are well-organized; (d) Open space zones are effectively used; (e) Active and comfortable pedestrian paths; (f) The marker serving as the identity of the space is very thick with Islamic religious values; (g) Supporting activities that take place simultaneously and in various ways are no longer centered on the east side of the mosque, but are spread out to the north side of the open space.Abstrak: Kabupaten Cianjur merupakan salah satu kota dengan alun-alun sebagai ruang terbuka publik yang memiliki sejarah panjang. Alun-alun merupakan ciri khas sebuah wilayah pusat pemerintahan kerajaan yang memiliki makna khusus sejak zaman kerajaan, zaman kolonial sampai dengan saat ini. Settingruang alun-alun berubah dari masa ke masa, sesuai dengan kebijakan penguasa pada masanya. Penelitian ini menggunakan metode eksploratif dengan teknik pengambilan data observasi lapangan. Terdapat tujuh dari delapan komponen pembentuk ruang kota yang ditemukan di Alun-alun Cianjur, diantaranya: (a) tata guna lahan yang mengalami perubahan; (b) Betuk ruang yang tidak lagi simetris seperti bentuk aslinya, dari terpusat menjadi linier dan konfigurasi masa bangunan yang tetap; (c) Sirkulasi dan ruang parkir yang tertata dengan baik; (d) zona ruang terbuka termanfaatkan dengan efektif; (e) Jalur pedestrian yang aktif dan nyaman; (f) Penanda sebagai identitas ruang sangat kental dengan nilai religius islami; (g) Kegiatan pendukung yang belangsung secara simultan dan beragam, tidak lagi terpusat di sisi timur masjid, namun tersebar ke sisi utara ruang terbuka.